The Role of Indonesian Local Wisdom in Shaping Male Students’ Academic Honesty in the Age of AI Tools - Bangkara, B.M.A.S. Anaconda (Politeknik Siber Cerdika Internasional, 2025)
This study investigates why Indonesian male university students choose to remain honest in their academic work despite the growing availability of AI-based tools that can be misused for cheating. Drawing on the Theory of Planned Behavior (TPB), the research examines how attitude toward honest behavior (ATB), subjective norms (SN), perceived behavioral control (PBC), behavioral intention (BI), and actual honest behavior (AB) are interrelated. Data were collected through an online survey of 350 male undergraduate students across Indonesia who had experience using generative AI tools such as ChatGPT, QuillBot, or Perplexity. The measurement and structural models were analyzed using Structural Equation Modeling (SEM) with AMOS. Results show that all TPB paths are statistically significant: positive attitudes, supportive social expectations, and strong perceived behavioral control each contribute meaningfully to students’ intentions to act honestly, and these intentions, in turn, strongly predict actual honest behavior. The model demonstrated excellent fit (CFI = .992, RMSEA = .017, CMIN/DF = 1.095), indicating that the proposed framework robustly explains honest academic conduct in this context. Beyond psychological determinants, the findings suggest that Indonesian cultural values—such as jujur (honesty), amanah (trustworthiness), tanggung jawab (responsibility), and malu (sense of shame)—reinforce students’ motivation to uphold integrity, even when AI-enabled shortcuts are convenient and difficult to detect. The study extends TPB applications by shifting the focus from explaining cheating to understanding the drivers of honesty and offers practical implications for designing integrity policies, educational programs, and AI-related guidelines that are both ethically grounded and culturally responsive.